Sweet talking rancher - Pearce, Kate, 1963- (Pearce, Kate, 1963- Millers of Morgantown., 2021)
Everyone in rancher Danny Miller's life wants to know how he feels about his teenage flame returning to Morgan Valley, California. Danny wishes he knew. After the disastrous ending of their relationship, and Faith's choice to leave town all those years ago, Danny's rebuilt his life without her. But he's about to have a very practical reason for needing her in it again--despite the very impractical desire she inspires once he lays eyes on her... Faith McDonald hadn't planned on returning home, but with her dad retiring, her help is needed at the family veterinary practice. She's hoping that by now, folks have forgotten what happened between her and Danny--even if the two of them never can. With a mystery infection decimating the Miller cattle, she and Danny soon find themselves on the same side for the first time in forever. There was a lot of trouble in their past, but the good parts never really flamed out, including their intense attraction. And their shared determination to cure the cattle might just lead them to a healing of their own--and a whole new all-grown-up future...